2011
DOI: 10.1007/s10658-011-9782-6
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Arabidopsis roots by Trichoderma atroviride promotes growth and enhances systemic disease resistance through jasmonic acid/ethylene and salicylic acid pathways

Abstract: Trichoderma spp. are common soil fungi used as biocontrol agents due to their capacity to produce antibiotics, induce systemic resistance in plants and parasitize phytopathogenic fungi of major agricultural importance. The present study investigated whether colonization of Arabidopsis thaliana seedlings by Trichoderma atroviride affected plant growth and development. Here it is shown that T. atroviride promotes growth in Arabidopsis. Moreover, T. atroviride produced indole compounds in liquid cultures. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
137
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(159 citation statements)
references
References 33 publications
15
137
0
7
Order By: Relevance
“…In accordance with previous studies in which root application of T. harzianum or T. atroviride was able to reduce the leaf lesion area caused by B. cinerea (49,54,55), T. parareesei T6 also triggered ISR against this foliar pathogen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies in which root application of T. harzianum or T. atroviride was able to reduce the leaf lesion area caused by B. cinerea (49,54,55), T. parareesei T6 also triggered ISR against this foliar pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…Root colonization by Trichoderma triggers a systemic response signaled by JA/ET in a way similar to that described for rhizobacteria (47). Systemic defenses induced by Trichoderma are also signaled by SA (48,49), though they vary depending on the plant genetic background, the interaction time, and the strain and inoculum size (5,50). In the present study, the in vitro assay showed that T. parareesei triggers defense responses against pathogens and salt stress in tomato seedlings.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with published reports (Contreras-Cornejo et al, 2011;Salas-Marina et al, 2011), our results show systemic protection against B. cinerea in WT-colonized Ar. thaliana plants compared with control plants.…”
Section: Discussionsupporting
confidence: 93%
“…T. harzianum strain T-22 is the only microbe reported to induce systemic resistance to pathogens in model plants (Contreras-Cornejo et al, 2011;Salas-Marina et al, 2011;Yoshioka et al, 2012) and also in maize indicative of its unique ability (Harman et al 2012). Induced systemic resistance is believed to be one of the most important mechanisms of biocontrol effects of Trichoderma (Harman, 2006).…”
Section: Induced Resistancementioning
confidence: 99%